Healing patterns after subgingival placement of a resin-modified glass-ionomer restoration: A histometric study in dogs - Santamaría, Mauro Pedrine [UNESP]; Suaid, Fabricia Ferreira; Carvalho, Marcelo Diniz; Nociti Júnior, Francisco Humberto; Casati, Marcio Zaffalon; Sallum, Antonio Wilson; Sallum, Enilson Antônio (Quintessence Publishing, 2013)
The aim of this study was to evaluate, clinically and histometrically, the effects of subgingival placement of a resin-modified glass-ionomer restoration during flap surgery. Nine dogs were included in this study. The mandibular canines were randomly assigned to receive either a transgingival resin-modified glass-ionomer restoration (test group) or no restoration (control group). The apical margins of the restorations in the test group and a reference notch on those in the control group were placed at the level of the bone crest. Clinical parameters were recorded 7 days before sacrifice. The dogs were sacrificed after 107 days, and undecalcified sections were obtained for histologic evaluation. Clinically, both groups presented significant clinical attachment loss and an increase in probing depth, but differences between groups were not statistically significant (P > .05). Histologically, a significant difference between groups was observed for length of epithelium (test, 4.05 ± 0.57 mm; control, 3.36 ± 0.63 mm; P = .01). The test group showed more bone resorption (2.02 ± 1.47 mm) when compared with the control group (0.74 ± 0.37 mm) (P = .048). It can be concluded that even with the claimed favorable properties of resin-modified glass ionomer, the presence of the restoration within the biologic width causes increased migration of the apical epithelium and bone resorption. © 2013 by Quintessence Publishing Co Inc.